MANAGING CREDIT BUBBLES. Issue 3 (June 2016) - Martin, Alberto; Ventura, Jaume
Abstract: We study a dynamic economy where credit is limited by insufficient collateral and, as a result, investment and output are too low. In this environment, changes in investor sentiment or market expectations can give rise to credit bubbles, that is, expansions in credit that are backed not by expectations of future profits (i.e., fundamental collateral), but instead by expectations of future credit (i.e., bubbly collateral). Credit bubbles raise the availability of credit for entrepreneurs: this is the crowding‐in effect. However, entrepreneurs must also use some of this credit to cancel past credit: this is the crowding‐out effect. There is an "optimal" bubble size that trades off these two effects and maximizes long‐run output and consumption. The equilibrium bubble size depends on investor sentiment, however, and it typically does not coincide with the "optimal" bubble size. This provides a new rationale for macroprudential policy. A credit management agency (CMA) can replicate the "optimal" bubble by taxing credit when the equilibrium bubble is too high and subsidizing credit when the equilibrium bubble is too low. This leaning‐against‐the‐wind policy maximizes output and consumption. Moreover, the same conditions that make this policy desirable guarantee that a CMA has the resources to implement it.